Salvage robot‐assisted radical prostatectomy with pelvic lymph node dissection for radiorecurrent prostate cancer in a patient with a previous history of rectal cancer surgery - Naoki Imasato; Shugo Yajima; Ryo Andy Ogasawara; Minoru Inoue; Kohei Hirose; Ken Sekiya; Madoka Kataoka; Yasukazu Nakanishi; Hitoshi Masuda (IJU Case Reports, 2025)
Introduction Severe adhesions render salvage robot‐assisted radical prostatectomy challenging in the treatment of patients with prostate cancer who have previously undergone colorectal cancer surgery. Case presentation A 76‐year‐old Japanese man who had previously undergone low anterior resection for rectal cancer presented with an elevated prostate‐specific antigen level, indicating a recurrence of prostate cancer that had been treated with intensity‐modulated radiation and androgen deprivation therapies. During the salvage robot‐assisted radical prostatectomy with pelvic lymph node dissection, severe adhesions were noted between the posterior aspect of the prostate and the intestine. The adhesions were successfully dissected under digital rectal examination and transrectal ultrasound guidance. Conclusion Salvage robot‐assisted radical prostatectomy after rectal cancer can be challenging. The use of transrectal ultrasound and digital rectal examination can facilitate the procedure. Screening for prostate cancer prior to colorectal cancer surgery could potentially allow for simultaneous resections.